PENANAMAN NILAI-NILAI PENDIDIKAN AGAMA ISLAM PADA PENDIDIKAN ANAK USIA DINI MELALUI METODE MONTESSORI DI SAFA ISLAMIC PRESCHOOL - Burhan Nudin (Millah: Journal of Religious Studies, 2016)
This study reviews the learning values of Islamic religious education and educational values instilled in early childhood through the Montessori method, which is a method of educating children in accordance with nature. Application of this method is tested in SAFA IslamicPreschool. It was found that the Montessori method in instilling the values of Islamic religious education in early childhood can be seen from the changes in attitudes and behavior of children an early age to get better and focus shown by courteous behavior, do good to fellow friends and come to the school to shake hands with their teachers